Border cities and territorial development - Medeiros, E. (Beyond Borders: Breakfast Debates - Border cities: champions of development and integration in cross border regions, 2022)
• Good morning. First of all, I would like to congratulate the organisation, and especially Ricardo for organising this Border Breakfast workshop on Border Cities and Territorial Development which follows from the publication of a recent book with the same title with European and North American case studies. Three other authors on European cases are speakers. • For the ones who do not know me, I am a Geographer and live in the Lisbon Metropolitan Area which has nothing to do with border areas. So, why do I research border cities and border areas? Mainly because I study the main territorial impacts of EU Cohesion Policy and have made a PhD comparing the impacts of two EU Interreg-A programmes (Portugal- Spain and Sweden-Norway). • As a Geographer I collect information via field work, and during my PhD I had the opportunity to cross the two studied borders in several main cross-border passages and noticed that the Interreg-A offices are not located on border cities but on regional capitals …. • What is a border city? • Why are border cities so important? • Border between Portugal and Spain … • Elvas and Badajoz – • Cross-border Planning – Solidify Institutional Networking and strategic planning with improved articulation between existing spatial plans at all territorial levels, extend sources of financing.